2020
DOI: 10.1177/1069072720956982
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Career Agency and Career Calling in Mid-Career: A Qualitative Investigation

Abstract: This qualitative study examined the perceptions of career agency and career calling among 35 U.S. mid-career foreign missionaries from four organizations who reported a sense of living out a calling. In-depth interviews were analyzed using grounded theory methodology to describe participant perspectives on calling and agency with the goal of understanding factors that contribute to living a calling. Data analysis revealed two main themes, nine categorical sub-themes, and 18 base concepts. The first theme, call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…Snell et al, 2015;Synard and Gazzola, 2018); career success (e.g. Montanari et al, 2021); career calling (Bott et al, 2017;Hunter et al, 2010;Lemke, 2021); career sustainability (Pak et al, 2020); women's careers (Abalkhail, 2020;Cho et al, 2019;Harman and Sealy, 2017;Osi and Teng-Calleja, 2021); and expatriate careers (Ellis et al, 2020;Shortland, 2020). Despite its contribution to careers scholarship in the last twenty years or so, however, qualitative research was hitherto located at the "margins" of the field (Blustein et al, 2005).…”
Section: Qualitative Studies and Careers Scholarshipmentioning
confidence: 99%
“…Snell et al, 2015;Synard and Gazzola, 2018); career success (e.g. Montanari et al, 2021); career calling (Bott et al, 2017;Hunter et al, 2010;Lemke, 2021); career sustainability (Pak et al, 2020); women's careers (Abalkhail, 2020;Cho et al, 2019;Harman and Sealy, 2017;Osi and Teng-Calleja, 2021); and expatriate careers (Ellis et al, 2020;Shortland, 2020). Despite its contribution to careers scholarship in the last twenty years or so, however, qualitative research was hitherto located at the "margins" of the field (Blustein et al, 2005).…”
Section: Qualitative Studies and Careers Scholarshipmentioning
confidence: 99%
“…(2017) found that nearly half of physicians were influenced by family members who were employed as health professionals or demonstrated values that informed the physicians’ callings. Results from in‐depth interviews suggest that the contextual factors, including cultural setting, life hardships, personal health and growth, social support, and organizational support, have an important influence on the process of living out one's calling (Lemke, 2020). Albeit limited, these consistent findings across different methods and populations reveal that social support may play an important role in the development of career calling.…”
Section: Social Support and Career Callingmentioning
confidence: 99%
“…One of the foundational elements of this study was the finding that perceiving a calling and living out a calling may be cyclical, as proposed by WCT, meaning that perceiving a calling may motivate individuals to pursue that calling (Vianello et al, 2020). Finally, two studies used WCT as a partial framework examining the influence of career adaptability on career agency (Lemke, 2021;Shava & Chinyamurindi, 2020). In Lemke's (2021) qualitative study, WCT served as a framework to evaluate predictors, moderators, and outcomes of calling.…”
Section: Definition or Partial Frameworkmentioning
confidence: 99%
“…Finally, two studies used WCT as a partial framework examining the influence of career adaptability on career agency (Lemke, 2021;Shava & Chinyamurindi, 2020). In Lemke's (2021) qualitative study, WCT served as a framework to evaluate predictors, moderators, and outcomes of calling. Lemke found evidence supporting WCT, suggesting calling can be a dynamic or cyclical experience, and recommended further exploration of sociocontextual factors based on themes that emerged in the study.…”
Section: Definition or Partial Frameworkmentioning
confidence: 99%